1982
DOI: 10.1121/1.387995
|View full text |Cite
|
Sign up to set email alerts
|

Input impedance of the cochlea in cat

Abstract: Tones were delivered directly to the stapes in anesthetized cats after removal of the tympanic membrane, malleus, and incus. Measurements were made of the complex amplitudes of the sound pressure on the stapes PS, stapes velocity VS, and sound pressure in the vestibule PV. From these data, acoustic impedance of the stapes and cochlea ZSC delta equal to PS/US, and of the cochlea alone ZC delta equal PV/US were computed (US delta equal to volume velocity of the stapes = VS X area of the stapes footplate). Some m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
140
1
4

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(153 citation statements)
references
References 25 publications
8
140
1
4
Order By: Relevance
“…Increasing Poisson_s ratio to 0.4 for the soft tissues in this model produced displacement changes of less than 10%, consistent with previous modeling (e.g., Qi et al 2004). This is also consistent with the theoretical relationship G = E/2(1 + u) between Poisson_s ratio (u), Young_s modulus (E), and the shear modulus (G), and the assumption that the annular ligament primarily operates in shear (Lynch et al 1982). This relationship predicts that the effect of increasing Poisson_s ratio to 0.5 would be only about 15% for the annular ligament.…”
Section: Geometry and Materials Propertiessupporting
confidence: 87%
See 1 more Smart Citation
“…Increasing Poisson_s ratio to 0.4 for the soft tissues in this model produced displacement changes of less than 10%, consistent with previous modeling (e.g., Qi et al 2004). This is also consistent with the theoretical relationship G = E/2(1 + u) between Poisson_s ratio (u), Young_s modulus (E), and the shear modulus (G), and the assumption that the annular ligament primarily operates in shear (Lynch et al 1982). This relationship predicts that the effect of increasing Poisson_s ratio to 0.5 would be only about 15% for the annular ligament.…”
Section: Geometry and Materials Propertiessupporting
confidence: 87%
“…The lateral bundle is about 160 mm in height and 50 mm in length, and its width varies between about 130 and 200 mm. The Young_s modulus of the SAL was set to 10 kPa, in line with vestibular sound pressure measurements by Lynch et al (1982). This value was also used by Sun et al (2002).…”
Section: Geometry and Materials Propertiesmentioning
confidence: 99%
“…We assumed the Young's modulus of the stapedial annular ligament to be 10 kPa, as estimated by Lynch et al (1982) in the cat. A recent measurement by Gan et al (2011) in human temporal bones reported a shear modulus of 3.6 kPa for the smallest measured shear stress.…”
Section: Baseline Materials Propertiesmentioning
confidence: 99%
“…6) incorporates the measurements of the geometry of the ear canal (37), the 3D asymmetrical geometry of the eardrum (3), the details of the eardrum fiber structure (11), a simple lever model for the ossicles terminated by known values for the cochlear impedance (38), and radiation damping representing the open middle-ear cavity.…”
Section: Methodsmentioning
confidence: 99%